Anti-MDA5 dermatomyositis: an update from bench to bedside. Issue 6 (12th November 2022) - Fuzzi, Enrico; Gatto, Mariele; Zen, Margherita; Franco, Chiara; Zanatta, Elisabetta; Ghirardello, Anna; Doria, Andrea
Abstract : Purpose of review: This review summarizes the recent developments about anti-MDA5 antibody positive dermatomyositis with a focus on its pathogenesis, clinical features and treatment options of rapidly progressive interstitial lung disease, its most ominous complication. Recent findings: Anti-MDA5+ dermatomyositis has a heterogeneous clinical spectrum with different patient subsets exhibiting widely different outcomes; severe acute interstitial lung disease is the main factor impacting prognosis. The pathogenetic role of anti-MDA5 antibodies is an active area of investigation. Summary: Anti-MDA5+ dermatomyositis has a wider spectrum of manifestations than previously thought. A high index of suspicion is needed not to miss atypical presentations. In the setting of acute interstitial lung involvement, once a confident diagnosis is made, an aggressive approach with early combined immunosuppression affords the best chances of survival.